Structural Model of Fundamental Decisions of Parental Involvement and Its Types Based on The Gender (Male and Female) of Elementary School Students - Nezamparast , Mahbobe; Talepasand, Siavash; Moradi, Shahab (Journal of Assessment and Research in Applied Counseling (JARAC), 2023)
Objective: The current research aimed to construct a structural model of the fundamental decisions of parental involvement and its forms based on the gender (male and female) of elementary school students. Materials and Methods: The design of this research was correlational, employing modeling methods. The study population consisted of all elementary school students in Tehran for the academic year 2020-21. The sample included 386 parents of these students, selected through random cluster sampling. The data collection tools in this research included 6 scales present in the Hoover-Dempsey and Sandler (2005) model of parental involvement. The data of this research were analyzed using SPSS23 and SMART PLS software, employing structural equation modeling as the statistical analysis method. Findings: The findings of the research showed that the latent construct of forms of parental involvement has a direct structural effect on the latent construct of school-based behaviors. The latent construct of forms of parental involvement also has a direct structural effect on the latent construct of home-based behaviors. The latent construct of forms of parental involvement with the latent construct of school-based behaviors is significantly moderated by gender. The latent construct of forms of parental involvement with the latent construct of home-based behaviors is also significantly moderated by gender, meaning that gender plays a moderating role between the variables, and parental involvement of sons at home is more than that of daughters. Conclusion: The study concludes that parental involvement in children’s education is significantly influenced by the gender of the child, with sons experiencing more involvement at home compared to daughters. Both home-based and school-based parental behaviors are directly affected by the forms of parental involvement, highlighting the critical role of gender as a moderating factor in these educational dynamics.